65.14.5 problem 26.1 (v)

Internal problem ID [13821]
Book : AN INTRODUCTION TO ORDINARY DIFFERENTIAL EQUATIONS by JAMES C. ROBINSON. Cambridge University Press 2004
Section : Chapter 26, Explicit solutions of coupled linear systems. Exercises page 257
Problem number : 26.1 (v)
Date solved : Tuesday, January 28, 2025 at 06:04:44 AM
CAS classification : system_of_ODEs

\begin{align*} \frac {d}{d t}x \left (t \right )&=2 x \left (t \right )+5 y \left (t \right )\\ \frac {d}{d t}y \left (t \right )&=-2 x \left (t \right )+\cos \left (3 t \right ) \end{align*}

With initial conditions

\begin{align*} x \left (0\right ) = 2\\ y \left (0\right ) = -1 \end{align*}

Solution by Maple

Time used: 0.276 (sec). Leaf size: 65

dsolve([diff(x(t),t) = 2*x(t)+5*y(t), diff(y(t),t) = -2*x(t)+cos(3*t), x(0) = 2, y(0) = -1], singsol=all)
 
\begin{align*} x \left (t \right ) &= -\frac {16 \,{\mathrm e}^{t} \sin \left (3 t \right )}{111}+\frac {69 \,{\mathrm e}^{t} \cos \left (3 t \right )}{37}-\frac {30 \sin \left (3 t \right )}{37}+\frac {5 \cos \left (3 t \right )}{37} \\ y \left (t \right ) &= -\frac {121 \,{\mathrm e}^{t} \sin \left (3 t \right )}{111}-\frac {17 \,{\mathrm e}^{t} \cos \left (3 t \right )}{37}-\frac {20 \cos \left (3 t \right )}{37}+\frac {9 \sin \left (3 t \right )}{37} \\ \end{align*}

Solution by Mathematica

Time used: 0.209 (sec). Leaf size: 418

DSolve[{D[x[t],t]==2*x[t]+5*y[t],D[y[t],t]==-2*x[t]+Cos[3*t]},{x[0]==2,y[0]==-1},{x[t],y[t]},t,IncludeSingularSolutions -> True]
 
\begin{align*} x(t)\to \frac {1}{3} e^t \left (-(\sin (3 t)+3 \cos (3 t)) \int _1^0-\frac {5}{6} e^{-K[1]} \sin (6 K[1])dK[1]+(\sin (3 t)+3 \cos (3 t)) \int _1^t-\frac {5}{6} e^{-K[1]} \sin (6 K[1])dK[1]-5 \sin (3 t) \int _1^0\frac {1}{3} e^{-K[2]} \cos (3 K[2]) (3 \cos (3 K[2])+\sin (3 K[2]))dK[2]+5 \sin (3 t) \int _1^t\frac {1}{3} e^{-K[2]} \cos (3 K[2]) (3 \cos (3 K[2])+\sin (3 K[2]))dK[2]-3 \sin (3 t)+6 \cos (3 t)\right ) \\ y(t)\to -\frac {1}{3} e^t \left (-2 \sin (3 t) \int _1^0-\frac {5}{6} e^{-K[1]} \sin (6 K[1])dK[1]+2 \sin (3 t) \int _1^t-\frac {5}{6} e^{-K[1]} \sin (6 K[1])dK[1]+3 \cos (3 t) \int _1^0\frac {1}{3} e^{-K[2]} \cos (3 K[2]) (3 \cos (3 K[2])+\sin (3 K[2]))dK[2]-3 \cos (3 t) \int _1^t\frac {1}{3} e^{-K[2]} \cos (3 K[2]) (3 \cos (3 K[2])+\sin (3 K[2]))dK[2]-\sin (3 t) \int _1^0\frac {1}{3} e^{-K[2]} \cos (3 K[2]) (3 \cos (3 K[2])+\sin (3 K[2]))dK[2]+\sin (3 t) \int _1^t\frac {1}{3} e^{-K[2]} \cos (3 K[2]) (3 \cos (3 K[2])+\sin (3 K[2]))dK[2]+3 \sin (3 t)+3 \cos (3 t)\right ) \\ \end{align*}